2022
DOI: 10.3889/oamjms.2022.9809
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Patient Satisfaction in Private Clinical Laboratories toward Patient Loyalty with Switching Cost and Location as Moderating Factors (An Empirical Study from Indonesia)

Abstract: BACKGROUND: Clinical laboratory services are at the forefront to support healthcare services, particularly during the pandemic of COVID-19. The increasing number of private clinical laboratories at present days indicates the increase in patient needs, causing the healthcare service provider to face challenges as people have more options. Therefore fostering patient loyalty (PL) is a crucial success factor for the business growth of clinical laboratories as healthcare providers.   AIM: The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…The result of this technical quality aspect is aligned with the results of the previous study's demonstrated positive effect (Levana and Antonio 2022;Khatri and Sharma 2021;Almatrafi et al 2018). This study revealed that patients mostly feel the PHP that involves interaction between the patient and the medical staff has a major role in creating their experience.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The result of this technical quality aspect is aligned with the results of the previous study's demonstrated positive effect (Levana and Antonio 2022;Khatri and Sharma 2021;Almatrafi et al 2018). This study revealed that patients mostly feel the PHP that involves interaction between the patient and the medical staff has a major role in creating their experience.…”
Section: Discussionsupporting
confidence: 88%
“…This can be seen from how the blood-taking process is carried out by medical staff; whether it makes the patient feel sick, scared, or even the patient feels nothing because the process is carried out very well, it can bring up an experience for the patient where the patient will give a good or bad description of his experience. Previous research shows a positive relationship between the PHP to patient satisfaction (Levana and Antonio 2022;Almatrafi et al 2018).…”
Section: Hypothesis 5 (H5) Laboratory Ambience Has a Positive Effect ...mentioning
confidence: 95%
See 3 more Smart Citations